Parent Health Beliefs, Social Determinants of Health, and Child Health Services Utilization among US School-Age Children with Autism - Zuckerman, Katharine Elizabeth (J Dev Behav Pediatr, 2015)
OBJECTIVE: Substantial variation exists in ASD care by race, ethnicity, and socioeconomic status; however, the role of parent health beliefs in this variation is poorly understood. Study goals were to (1) examine variation in parent beliefs about ASD prognosis and treatment according to social determinants of health (SDH) and (2) assess whether this variation was associated with variable health services utilization, among 1420 children with special health care needs (CSHCN) having autism spectrum disorder (ASD). METHODS: We used linked data from the 2011 Survey of Pathways to Diagnosis and Treatment and the 2009/10 National Survey of Children with Special Health Care Needs. Bivariate and multivariate analyses assessed variation in parent beliefs according to race/ethnicity, household income, and parent educational attainment. Further analyses assessed whether variation in beliefs was associated with use of psychotropic medication, traditional therapy, or complementary/alternative therapy for ASD. RESULTS: Parents of lower educational attainment or who had lower income were more likely to think that their child’s condition was a mystery. Near-poor families were less likely to feel they had the power to change the child’s condition. Parents of minority children were more likely than white children to view their child’s condition as temporary. However, these differences in beliefs only had modest associations with variation in use of the health services analyzed. CONCLUSIONS: Some SDH-related variation exists in health beliefs among parents of children with ASD, but these differences may not be the main factors accounting for ASD health care disparities.